Wood mimetic hydrogel beads for enzyme immobilization. (22nd January 2015) - Park, Saerom; Kim, Sung Hee; Won, Keehoon; Choi, Joon Weon; Kim, Yong Hwan; Kim, Hyung Joo; Yang, Yung-Hun; Lee, Sang Hyun
Highlights: Preparation of wood mimetic hydrogel bead using ionic liquid. Entrapment of lipase into wood mimetic bead. Highly enhanced stability of lipase in wood mimetic bead. Abstract: Wood component-based composite hydrogels have potential applications in biomedical fields owing to their low cost, biodegradability, and biocompatibility. The controllable properties of wood mimetic composites containing three major wood components are useful for enzyme immobilization. Here, lipase from Candida rugosa was entrapped in wood mimetic beads containing cellulose, xylan, and lignin by dissolving wood components with lipase in [Emim][Ac], followed by reconstitution. Lipase entrapped in cellulose/xylan/lignin beads in a 5:3:2 ratio showed the highest activity; this ratio is very similar to that in natural wood. The lipase entrapped in various wood mimetic beads showed increased thermal and pH stability. The half-life times of lipase entrapped in cellulose/alkali lignin hydrogel were 31- and 82-times higher than those of free lipase during incubation under denaturing conditions of high temperature and low pH, respectively. Owing to their biocompatibility, biodegradability, and controllable properties, wood mimetic hydrogel beads can be used to immobilize various enzymes for applications in the biomedical, bioelectronic, and biocatalytic fields.